THE DOG AND THE PARAKEET: lacan among the animals. Issue 4 (2nd October 2017) - Buse, Peter
Abstract: This article explores the place of the animal and animals in Lacanian psychoanalysis, arguing that the standard accounts of Lacan on the animal, including the influential intervention by Derrida, depend almost exclusively on the Écrits and Lacan's early seminars, overlooking late Lacanian texts and seminars. It starts by examining perplexing instances in Lacan's seminar of "silliness" or "stupidity" – what he himself calls bêtises . The bêtise, which Lacan says plays a critical role in clinical practice, is then treated as the way into a discussion of the place of the animal in Lacan's seminar, and how it changes between early and late seminars. Écrits and the early seminars consistently locate animals in the imaginary while denying them access to the symbolic, a realm exclusive to the human animal at this stage of Lacan's thinking. The article then shows how this earlier work rests heavily on ethology, especially key figures such as Konrad Lorenz and Niko Tinbergen, who disappear entirely from the late Lacan, along with the assumption that animals are caught up purely in the imaginary. If the bees and rats of Seminar XX: Encore do not act as a language-less foil to the desiring human subject, the article asks, what function do they play in the later Lacan? Part of this reading is dedicated to a reassessment of Derrida's account of the animal in Lacan, an account which is often taken to be the final word on the subject.